The Restructuring of Non-Performing Financing AT ISLAMIC BANK (A Case Study at BANK BRI SYARIAH MALANG) - Munahar, Nailan Fadhila (Jurnal Ilmiah Mahasiswa FEB, 2016)
The number of Islamic banks has increased between 1992 and 2016. This does not guarantee there is an improvement in the performance of Islamic bank. Similar to conventional banks, Islamic banks have the same problem, which is non- performing financing (NPF). Bank Indonesia has issued a regulation related to non-performing financing. The main goal is to maintain the quality of financing. This study aims to investigate and analyze whether the BRI Syariah Malang has complied with Bank Indonesia regulations or it has made an adjustments related to Bank Indonesia Regulation No. 13/9 / PBI / 2011 concerning with the Bank Indonesia Regulation No. 10/18 / PBI / 2008 on Restructuring  Financing  for Islamic Banks and Sharia Business Units. This study uses a qualitative method. The results show that non-performing financing was dominated by Murabahah financing caused  by the economic flow  in Malang. The policy of Bank  BRI Syariah Malang related to restructuring non-performing financing has complied and  it  has  made an adjustment  related  to  the Bank  Indonesia regulation No. 13/9/PBI/2011 in terms of the implementation of restructuring non-performing financing,  the  Standard  Operating  Procedure  (SOP),  and  the  involvement  of Dewan Pengawas Syariah (DPS) in bank daily activities.Keywords: Restructuring, Islamic banks, non-performing financing, BRI Syariah Malang.